Unhealthy Snacking Habits are Prevalent Among Elementary School Students - Matondang, Riana Jogi Ahdareni; Yuliaty, Maria (Bina Nusantara University, 2024)
Development Index (HDI) showing a noteworthy increase in 2018. This progress is a promising sign for Indonesia's future, placing it in the high human development category. The focus of the report is on child welfare and health services, emphasizing the significance of adequate nutrition for proper growth and development. The report highlights the challenges parents face in providing their children with nutritious food due to their busy schedules, which often results in children buying unhealthy snacks at school. The 2019 Annual Report of the Food and Drug Supervisory Agency (BPOM) raises concerns regarding the quality of School Children's Snack Food (PJAS). A significant portion of these snacks did not meet the required standards and were found to be high in sugar, salt, and fat. These unhealthy snacks pose a risk to children's health, leading to health issues such as obesity, diabetes, and hypertension. Moreover, the report notes that poor nutrition not only affects children's health but also their academic performance. By using qualitative research, this report aims to describe the social condition and its impact on the unhealthy snacks habit in school. This report highlights the critical role proper nutrition plays in children's health and academic performance. It underscores the need for parents and schools to work together to provide healthy and nutritious food options for children. Furthermore, the report suggests that schools can play a pivotal role in promoting healthy eating habits by educating children about the importance of proper nutrition and offering healthy food options.